(untitled) (Ameghiniana, 2013)
Some petrified fragments of a stem found in El Tranquilo Formation (Triassic) are referred to a new species of Osmundites, 0. herbstii. They are found in the same bed with a frond of Cladophlebis sp. The preservation is prior for making detailed anatomical study, .but sufficient for specific diagnosis. This new species is based mainly on the different pattern .presented by the distribution of mechanical tissue in the petioles, and the number of. meristeles in the central vascular cylinder.